Transcription factor YY1-activated GNG5 facilitates glioblastoma cell growth, invasion, stemness and glycolysis through Wnt/β-catenin pathway - Sheng Liang; Liangliang Zhu; Feng Yang; Haijun Dong (Scientific Reports)
Abstract G protein subunit Gamma 5 (GNG5) has been found to be involved in regulating glioma progression. However, its function and mechanism in glioblastoma (GBM) progression need to be further elucidated. GBM cell proliferation, apoptosis, invasion and stemness were assessed by cell counting kit 8 assay, EdU assay, flow cytometry, transwell assay and sphere formation assay. The mRNA and protein levels of GNG5 and Yin Yang 1 (YY1) were determined by quantitative real-time PCR and western blot (WB). Detection of the glucose consumption, lactate production and ATP/ADP ratios were used to assess cell glycolysis. Besides, Wnt/β-catenin pathway-related protein levels were examined by WB. Mice xenograft model was also constructed to explore GNG5 roles in vivo. GNG5 was highly expressed in GBM, and its silencing inhibited GBM cell proliferation, invasion, stemness and glycolysis, while promoted apoptosis. Transcription factor YY1 could bind to the GNG5 promoter region and induce its expression. GNG5 overexpression reversed the inhibitory effects of YY1 silencing on GBM cell growth, invasion, stemness and glycolysis. YY1/GNG5 axis could activate the Wnt/β-catenin pathway, and Wnt/β-catenin pathway agonists SKL2001 could revert the effects of GNG5 silencing on GBM cell progression. Furthermore, GNG5 facilitated GBM tumor growth by mediating the Wnt/β-catenin pathway. YY1-mediated GNG5 promoted GBM progression through the Wnt/β-catenin pathway.